2002
DOI: 10.1080/01411920120122149
|View full text |Cite
|
Sign up to set email alerts
|

Pupil Groupings in Primary School Classrooms: Sites for learning and social pedagogy?

Abstract: Studies of teaching and learning within classrooms rarely consider the multilayered effects of social context, especially involving within-class groupings. Yet, all pupils in classes are placed in some form of grouping throughout their classroom life and this will have an impact on their learning. This article seeks to move forward the understanding of within-class groupings in real classrooms. Five 'core themes' central to pupils' experience of groups in classrooms are identi ed (group size, group composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
7

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 21 publications
2
44
0
7
Order By: Relevance
“…Specifically, we have found that a larger proportion of boys (than girls) are assigned to work alone, which may reflect teacher's concern with control of behaviour and attention -a possibility further highlighted by the high level of adult presence (teacher and non-teacher) with these groupings (Kutnick, Blatchford & Baines, 2002). Group size and the ability mix of groups can also be connected.…”
Section: The Classroom Context: Preparing the Classroom And The Groupsmentioning
confidence: 74%
See 3 more Smart Citations
“…Specifically, we have found that a larger proportion of boys (than girls) are assigned to work alone, which may reflect teacher's concern with control of behaviour and attention -a possibility further highlighted by the high level of adult presence (teacher and non-teacher) with these groupings (Kutnick, Blatchford & Baines, 2002). Group size and the ability mix of groups can also be connected.…”
Section: The Classroom Context: Preparing the Classroom And The Groupsmentioning
confidence: 74%
“…The purpose was to provide a systematic, quantitative, and multi-dimensional description of grouping practices in relation to learning tasks, curriculum areas and year groups across the primary and secondary stages (see Blatchford, Baines, Kutnick & Martin, 2001;Blatchford et al, 1999;Blatchford, Kutnick, Clark, MacIntyre and Baines, 2001;Kutnick, Blatchford & Baines, 2002). Five core themes were investigated by use of a teacher completed classroom grouping map technique: the size and number of groups, group composition, e.g., in terms of ability of child and sex, adult presence in groups, the curriculum and task activities in groups, and the type of interaction between children in groups.…”
Section: : Background: the Current Place Of Group Work In Uk Schoolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Contemporary research vis-à-vis organisation of group work, for instance Baines, Blatchford, and Kutnick (2008) and Kutnick, Blatchford, and Baines (2002)) stresses the importance of finding an optimum combination of group size, mix of students, and nature of the task.…”
Section: Research Confirming the Students' Opinions About Organisatiomentioning
confidence: 99%